(untitled) (GEON Journal (Management, Organizations and Business), 2020)
The lack of motivation in employees is a problem that affects their work performance, having complications in their emotional and psychological health, regardless of the size or type of organization, productivity is reduced and the consequences are reflected in raising operating costs in general terms. This research sought to identify the degree of motivation that collaborators have in medium-sized companies in the city of Xalapa, Veracruz, Mexico, specifically in the functional areas of the organizational structure, aimed to make the diagnosis under the analysis of the theories of Motivation and human needs of Maslow to inquire in a general way how motivated they are and if they meet their needs according to this theory. A non-experimental, exploratory, descriptive and quantitative research was carried out; For this, a duly validated motivational instrument with 20 items divided by dimensions was administered, with indicators that measure the elements of the theory of needs and the motivation of the collaborators. The analysis units were determined based on an infinite population that was represented by 96 medium-sized companies, which were specifically surveyed in the functional area, being industrial, service and commercial companies. The results obtained showed that the surveyed personnel did not feel that their needs for recognition or self-fulfillment were mostly met, in the same sense, the statistical hypothesis test showed that more than 60% of the collaborators were not motivated by their work environment. Based on the aforementioned, it was concluded that it is necessary to establish clear goals both at the organizational and personal level in order to take advantage of the potential of the collaborators, in the same sense, design incentive programs, recognition of personal achievements and, if necessary, changes in the approach to work.